1997
DOI: 10.1002/(sici)1096-9063(199710)51:2<153::aid-ps615>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a wettable powder formulation for the nuclear polyhedrosis virus ofAnticarsia gemmatalis(Lep.: Noctuidae)

Abstract: : The inÑuence of di †erent carriers on the physical and biological stability of Baculovirus anticarsia wettable powder formulations was studied. The formulations were obtained by mixing the puriÐed polyhedra of B. anticarsia with a carrier and drying the suspension in a bench spray dryer. Bioassays with Anticarsia gemmatalis Hu bner showed that activity was maintained with the amorphous silica, attapulgite and kaolinite after a year of storage. In the presence of bentonite, activity declined 50% in the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This is not a critical problem in the intensive periurban horticulture systems of Kenya or South Africa, but it is certainly a problem in most of SSA and the poor farmers most at risk from armyworm who generally lack access to refrigerators for storing BCA. The AgNPV product is a cheap, air-dried kaolin-formulated biopesticide with good long-term storage properties (Medungno et al 1997). It has long been recognised that BCA should have a shelf-life of at least 2 years and preferably 4 years (Burges and Jones 1998) and, given the episodic outbreak pattern of armyworms, this is especially important for SpexNPV.…”
Section: Production Of Spexnpv For Poor Farmersmentioning
confidence: 99%
“…This is not a critical problem in the intensive periurban horticulture systems of Kenya or South Africa, but it is certainly a problem in most of SSA and the poor farmers most at risk from armyworm who generally lack access to refrigerators for storing BCA. The AgNPV product is a cheap, air-dried kaolin-formulated biopesticide with good long-term storage properties (Medungno et al 1997). It has long been recognised that BCA should have a shelf-life of at least 2 years and preferably 4 years (Burges and Jones 1998) and, given the episodic outbreak pattern of armyworms, this is especially important for SpexNPV.…”
Section: Production Of Spexnpv For Poor Farmersmentioning
confidence: 99%
“…The evaluation of PIBs virulence was assayed in bioassays as described elsewhere (Medugno et al 1997). Briefly, PIBs were diluted in distilled water and 5ll of each dilution was applied to the surface of the larvae diet.…”
Section: Vıŕus Infection Pibs Production and Virulencementioning
confidence: 99%
“…However, samples of the same formulations stored at refrigerated temperatures for more than two years did not lose activity. Previous research with similar virus formulations (Tamez- Guerra et al 2002) showed reduced activity after storage at room temperatures for 1 yr. Medugno et al (1997) reported no loss of activity for three of four formulations of Anticarsia gemmatalis polyhedrosis virus prepared by spray drying with clays and stored at room temperature for 1 yr. Thus, higher storage temperatures seem well correlated with reduced insecticidal activity of baculovirus for both unformulated and formulated samples.…”
Section: Discussionmentioning
confidence: 99%